(untitled) (Architecture Image Studies, 2025)
This paper investigates the relationship between architectural design and its psychological effects on learning and personal development. It focuses on how elements such as spatial organization, lighting, color, and materials influence cognitive processes, emotional well-being, and social interactions within educational environments. Utilizing a comprehensive literature review and case study analysis of such educational institutions as Trinity College Dublin (TCD), École Polytechnique Fédérale de Lausanne (EPFL), and the University of Tokyo, the study identifies key design features that enhance engagement and collaboration among learners. Observational assessments provide essential information about student-teacher interactions within educational environments. Educational settings require purposeful architectural design to become productive spaces which support comprehensive personal development.